Long-Term Care of Older Persons in Lithuania: Public Perceptions and the Attitudes of Social Service Providers - Matonytė, Irmina; Kazlauskaitė, Rūta; Poškutė, Virginija (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in Lithuanian; abstract in English] In this paper, building on the welfare culture and public value management theories, we analyze the situation of long-term care (LTC) of older persons in Lithuania. As the normative vantage point of the study, we hold that the objective of developing and maintaining a harmonious and sustainable LTC system requires developing a system that is not only economically efficient but ensures that LTC services are of the right quality, are accessible and conform to public expectations as well as to the stakeholders’ and service providers’ attitudes. The review of prior research on social policy and LTC conducted in Lithuania shows that the attitudes of LTC providers as a community, as well as those of different stakeholders, toward the role of the state, family and other institutions in the provision of LTC vary to a considerable extent, between the social work and health care systems in particular. However, this strand of research is lacking a broader conceptualization, i.e., a situation analysis in relation to the macro level of LTC developments, public values and stakeholder attitudes to LTC as a distinct field of social policy. Next, we outline the LTC situation in Lithuania. Then, we interpret public attitudes and the attitudes of social service providers toward the responsibility for the LTC as a complex reaction to the current unsatisfactory LTC situation in the country. Surveys show that an expectation still prevails in the society that LTC should be provided by family members and other close persons, which emphasizes a need for an active discussion of LTC responsibilities and the actual situation among the politicians and society at large. The findings of our LTC stakeholder survey (n=260) show that LTC providers also believe families to be the most important pillar supporting LTC. On the other hand, a more or less equal distribution of LTC providers into two groups regarding the increase or reduction of taxes and investment into social protection indicates a need for a wider discussion of this issue among LTC providers, as the current situation points to an absence of an interest group in the field of LTC that would hold a clear position about service demand and the possible means for meeting it. We conclude with recommendations on the enhancement of democratic deliberations and other instruments proposed by public value management, which would in turn allow to better conform to the attitudes and expectations of all the stakeholders and match their interests in the LTC domain.